PEMBUATAN KUE PANEKUK - Rudy Pramono; Fiona Tri Utami Jaya; Meilissa Octavia; Yesis Christie Laatung (Jurnal Sinergitas PKM & CSR, 2017)
Pancake is the one of the most common food and easy to find. Which is this menu is easy to prepare also. As for the materials pancake is consist of flour, egg, and water. But in practice in Indonesia, many people make pancakes using domestic chickhen egg, which is easy to use and cheaper price that other eggs. This study is a product development research. Based on the assessment of the expert pastry, 32 potential consumers, as well as the price analysis can be concluded that the pancake that uses basic ingredients quail egg is a pancake that is acceptable among the general public. Pancake has potential for productive businesses for housewives as a source of income.